Molecular detection of albinism gene in Brazilian buffalo herds (Bubalus bubalis) - Bernardino, Pedro N. [UNESP]; Martins, Aline F.A. [UNESP]; Barbosa, José D.; Schild, Ana L.; Damé, Maria Cecília F.; Borges, Alexandre S. [UNESP]; Oliveira-Filho, José P. [UNESP] (FapUNIFESP (SciELO), 2019)
Albinism is a genetic disease characterized by deficient melanin production making affected animals more susceptible to skin problems, negatively influencing production systems of the same. In buffalo, a nonsense mutation (c.1431G>A) in the tyrosinase gene was already described, which is responsible for the oculocutaneous albinism buffalo phenotype. However, prevalence studies have never been performed for this anomaly in Brazil. Therefore, the objective of this study was to investigate this mutation in buffalo herd in Brazil. Of the 315 buffalo tested with no albinism phenotype evident, 11 (3.5%) were heterozygous for the mutation and none were mutated homozygous, showing the existence of the albinism gene in buffalo production herds and proving the importance of prevalence studies for hereditary diseases in order to prevent the dissemination of these same genes and their negative productivity consequences.